2014
DOI: 10.1016/j.stem.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA Maturation to Initiate Heterochromatin Formation in the Nucleolus Is Required for Exit from Pluripotency in ESCs

Abstract: The open chromatin of embryonic stem cells (ESCs) condenses into repressive heterochromatin as cells exit the pluripotent state. How the 3D genome organization is orchestrated and implicated in pluripotency and lineage specification is not understood. Here, we find that maturation of the long noncoding RNA (lncRNA) pRNA is required for establishment of heterochromatin at ribosomal RNA genes, the genetic component of nucleoli, and this process is inactivated in pluripotent ESCs. By using mature pRNA to tether h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
187
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(202 citation statements)
references
References 58 publications
(76 reference statements)
14
187
0
1
Order By: Relevance
“…First, in accordance with enhanced protein synthesis, our results and previous transcriptome/proteome data show that SSUP genes are up-regulated in undifferentiated cells compared with their differentiated counterparts. Consistently, the rDNA promoter is unmethylated and kept in an open state in mESCs, producing a high level of pre-rRNA (Savic et al 2014). Second, as pluripotent stem cells divide rapidly, they have a high demand for protein synthesis to support their unusually accelerated proliferation.…”
Section: Ssup Is Necessary For Esc Maintenancementioning
confidence: 99%
“…First, in accordance with enhanced protein synthesis, our results and previous transcriptome/proteome data show that SSUP genes are up-regulated in undifferentiated cells compared with their differentiated counterparts. Consistently, the rDNA promoter is unmethylated and kept in an open state in mESCs, producing a high level of pre-rRNA (Savic et al 2014). Second, as pluripotent stem cells divide rapidly, they have a high demand for protein synthesis to support their unusually accelerated proliferation.…”
Section: Ssup Is Necessary For Esc Maintenancementioning
confidence: 99%
“…ChIP has been recently described (73). For each ChIP assay, 30 μg of cross-linked and sonicated chromatin was incubated with 4 μg of antibody.…”
mentioning
confidence: 99%
“…A recent report has revealed that the maturation of pRNA, originated from the processing of an IGS lncRNA, is required for the establishment of heterochromatin at ribosomal RNA genes during ES cell differentiation (Savic et al, 2014). These data suggested that lncRNA regulates the structure and function of the nucleolus under environmental stimuli and during development.…”
Section: Prna and The Nucleolusmentioning
confidence: 97%